Medicinal plants and other non timber forest products in Himachal Pradesh : aspects of their status, usage and trade in Kullu and Mandi - Bajaj, Manjul (s.n.], 1997)
Study conducted for districts of Kulu and Mandi in Himachal Pradesh.